MANAGING CANNIBALISM AND IMPROVING LARVAL SURVIVAL IN BARRAMUNDI HATCHERY - Lesmana, Indra; Effendi, Irwan; Suharman, Indra; Putra, Iskandar; Ruthmawati, Abigael; Andesca, Yofi Devara (Asian Journal of Aquatic Sciences, 2025)
Barramundi (Lates calcarifer) are economically valuable and usually cultivated in tropical marine hatcheries. Their fertilization and hatching rates are generally high, but poor survivorship of larvae due to cannibalism and cohort mismanagement remains a problem. In this study, we sought to address field-based techniques for controlling cannibalism and augmenting larval survival in large-scale hatcheries at Balai Besar Perikanan Budidaya Laut (BBPBL), Lampung, Indonesia. A 30-day rearing cycle was completed through descriptive observation methods focused on reproduction, and growth monitoring was performed concerning feeder grade improvement. The recorded data indicated a fertilization rate of 86% alongside an impressive hatching rate of 96%. However, the survival rate dropped to 52%, primarily due to cannibalism. Considerable size disparity among cohorts, lack of grading during asynchronous growth periods, and stunted development seem to drive cannibalism under these conditions. Increasing the frequency or decreasing the size gap between assessments has proven effective in enhancing survival levels alongside better feeding synchronization, water quality management, and reduced particulate matter concentration in water tanks. These outcomes will assist tropical aquaculture systems with long-term sustainable frameworks while providing actionable insight to hatchery managers without further testing